CENFED spreads wings to Sabah, Sarawak - UMP, PNC (Penerbit UMP, 2010)
Universiti Malaysia Pahang's (UMP) Centre for Continuing Education & Professional Development, or fondly known as CENFED, has spread its wings to Sabah and Sarawak when it launched its Executive Diploma in Plantation Management & Technology Programme there recently.